2018
DOI: 10.1038/s41387-018-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Wheat-derived arabinoxylan oligosaccharides with bifidogenic properties abolishes metabolic disorders induced by western diet in mice

Abstract: BackgroundNon-digestible carbohydrates present in cereals such as fructans and arabinoxylans represent promising prebiotic nutrients to prevent the development of obesity and related metabolic disorders. OBJECTIVE AND DESIGN: The aim of this study was to determine the corrective effects of wheat bran-derived arabinoxylan oligosaccharides in obese mice fed a western diet (WD). WD was given for 4 weeks before wheat bran extract (WBE) supplementation (5%) for an additional 4 weeks, whereas a control group receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
0
24
1
1
Order By: Relevance
“…The positive effects of fiber on body weight gain have been reported previously in human studies and in rodents, where the improvements were associated with intestinal integrity and hepatic and systemic inflammation. [32][33][34] We speculated that the improvements in our study could be mediated through the restored production of SCFAs by gut microbiota acting on the fibers, as we observed significant changes in SCFA levels in response to oat and rye supplementation. Indeed, it has been suggested that SCFAs may induce or promote body weight reduction acting via specific SCFA receptors, GPR43, and GPR41.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of fiber on body weight gain have been reported previously in human studies and in rodents, where the improvements were associated with intestinal integrity and hepatic and systemic inflammation. [32][33][34] We speculated that the improvements in our study could be mediated through the restored production of SCFAs by gut microbiota acting on the fibers, as we observed significant changes in SCFA levels in response to oat and rye supplementation. Indeed, it has been suggested that SCFAs may induce or promote body weight reduction acting via specific SCFA receptors, GPR43, and GPR41.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study represents an approach in which AXOS is administered together in an enriched-fat diet to test its preventive effects [76]. Besides, recently, AXOS has shown beneficial effects when administered after the pre-treatment of 4 weeks with an obesogenic diet [79]. In the MyNewGut project, we have explored the potential synergic or complementary effects of different DF utilized by indigenous intestinal human bacteria that can constitute the next generation of probiotics.…”
Section: Mechanism Of Action Of Axos In Preclinical Animal Models Of mentioning
confidence: 99%
“…Previous studies have shown prebiotic-induced alleviation of NAFLD is dependent on achieving successful weight loss [19] , [20] , [21] , [22] , [23] , [24] , [25] . In contrast, in the current study we show that prebiotic consumption can improve hepatic steatosis in HFD-fed mice irrespective of weight loss which suggests that the prebiotics induced alterations in the gut microbiota might directly impact liver lipid metabolism via the gut-liver axis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, fructo-oligosaccharides supplementation reduced the accumulation of hepatic triglyceride by modulating the gut microbiota, increasing fatty acid oxidation and glucagon-like peptide 1 expression [20] . A variety of prebiotics such as inulin [21] , [22] , chitin-glucan [23] , polysaccharides from fungi [24] , arabinoxylan [25] have shown to alleviate NAFLD along with reduction in body weight in HFD-fed mice possibly via production of short chain fatty acids (SCFAs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation